2021
DOI: 10.3390/s21082583
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Users’ Spatial Familiarity on Their Emotional Perception of Space and Wayfinding Movement Patterns

Abstract: In order to evaluate the sensory perceptions of users who visited a train station, this study aimed to conduct an evaluation of their spatial emotions and identify the distance and type of transfer. For evaluation and verification, emotional recognition and wayfinding types were analyzed according to types in the groups (gender, age, and spatial familiarity) of experimental participants. There were two research questions: “Will the length of movement patterns in the experiment environment vary depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…User characteristic record: Before use, mobile AR nav-igation can record the user's gender, mental cutting ability, and other characteristics, and then set the most suitable AR navigation parameters [14]. Interface presentation: mobile AR navigation can try to provide men with a dynamic and technological interface to increase their excitement; show women a gentle, warmcolored interface to increase their sense of security in the AR navigation environment.…”
Section: A Characteristics Of Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…User characteristic record: Before use, mobile AR nav-igation can record the user's gender, mental cutting ability, and other characteristics, and then set the most suitable AR navigation parameters [14]. Interface presentation: mobile AR navigation can try to provide men with a dynamic and technological interface to increase their excitement; show women a gentle, warmcolored interface to increase their sense of security in the AR navigation environment.…”
Section: A Characteristics Of Usersmentioning
confidence: 99%
“…In the study of navi-gation in the virtual scenes, Halik and Kent [13] found that user differences will lead to the diversity of way-finding strategies, which can affect the effectiveness of navigation. Kim et al [14] showed that user differences have an impact on their spatial affective perception and movement patterns. Chen and Chen [15] investigated users' performance and subjective preferences for way-finding tasks in a 3D virtual enviro-nment and found that interaction mode plays a key role.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial familiarity is also an essential factor that affects wayfinding behavior in the environment and the weight of landmark indicators. Moreover, existing studies have investigated the effects of environmental familiarity on wayfinding (Kim, Choi, Han, & Kim, 2021; Meneghetti, Muffato, Toffalini, & Altoè, 2017; Muffato & Meneghetti, 2020), but few studies have applied user spatial familiarity preferences to practical pedestrian navigation systems.…”
Section: Related Workmentioning
confidence: 99%
“…These elements can make a participant feel uncomfortable, particularly since this environment is not something most people have experienced before. A participants' feelings and attitudes to such an experimental environment will ultimately play a role in their behaviour during the experiment (Kim et al, 2021;Scrafton, 2015).…”
Section: Experimental Design Of the Studymentioning
confidence: 99%